A Preorganized Metalloreceptor for Alkaline Earth Ions Showing Calcium Versus Magnesium Selectivity in Water: Biological Activity of Selected Metal Complexes. Issue 35 (28th July 2014) - Amatori, Stefano; Ambrosi, Gianluca; Fanelli, Mirco; Formica, Mauro; Fusi, Vieri; Giorgi, Luca; Macedi, Eleonora; Micheloni, Mauro; Paoli, Paola; Rossi, Patrizia
Abstract The N, N′‐bis[(3‐hydroxy‐4‐pyron‐2‐yl)methyl]‐N, N′‐dimethylethylendiamine (Malten=L) forms the highly stable [CuH−2L] species in water, in which the converging maltol oxygen atoms form an electron‐rich area able to host hard metal ions. When considering the alkaline earth series (AE), the [Cu(H−2L)] species binds all metal ions, with the exception of Mg2+, exhibiting the relevant property to discriminate Ca2+ versus Mg2+ at physiological pH 7.4; the binding of the AE metal is visible to the naked eye. The stability constant values of the trinuclear [AECu(H−2L)2]2+ species formed reach the maximum for Ca2+ (log K=7.7). Ca2+ also forms a tetranuclear [CaCu(H−2L)]24+ species at a high Ca2+ concentration. Tri‐ and tetranuclear calcium complexes show blue‐ and pink‐colored crystals, respectively. [Cu(H−2L)] is the most active species in inducing DNA alterations. The DNA damages are compatible with its hydrolytic cleavages.